Broken fragments and debris assembled on the southeast face of the adhisthana - Temples of India Project Team (Jio Institute, 2024)
Broken fragments and debris from the original temple assembled on the southeast face of the adhisthana. The stones are tightly arranged, richly detailed, and deeply carved, creating contrasting shadows that make the artwork look three-dimensional in sunlight. The carvings depict various types of flora and fauna as well as hybrid creatures like kinnaras, vyalas, and makara.